The Relationship Between Job Satisfaction and Psychological Well-being of Workers in Profit Companies - Ludia Utamima; Ninik Setiyowati (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2026)
Workers are a strategic asset that determines the success and competitiveness of for-profit companies. Workers’ psychological well-being is an important factor in sustaining performance. Employees tend to be more adaptive, resilient, and able to cope effectively with work-related pressures. One factor that influences psychological well-being is job satisfaction, which reflects an individual’s positive evaluation of several aspects of their work. This study aims to examine the relationship between job satisfaction and psychological well-being among employees in for-profit companies through a systematic literature review (SLR). The review followed PRISMA guidelines and involved the following stages: literature identification, screening, review, synthesis of results, and discussion. The search was conducted using VOSviewer and Publish or Perish across the Google Scholar and Scopus databases. Inclusion criteria were: publications from 2021–2025, use of Ryff’s psychological well-being theory, participants employed in for-profit companies, and quantitative studies with correlational designs. The findings indicate that job satisfaction has a significant positive relationship with psychological well-being. Higher job satisfaction is associated with higher psychological well-being, particularly in the dimensions of environmental mastery and personal growth. These results underscore the importance of job satisfaction as a predictor of employees’ psychological well-being in for-profit companies.